2019
DOI: 10.14531/ss2019.1.48-56
|View full text |Cite
|
Sign up to set email alerts
|

Total Arthroplasty and Anterior Cervical Discectomy With Fixation: Long-Term Results of a Randomized Clinical Trial

Abstract: Objective.To perform comparative analysis of the long-term results of using the methods of total cervical disc arthroplasty (CDA) and anterior cervical discectomy and fusion (ACDF) in the surgical treatment of patients with single-level degenerative diseases of cervical intervertebral discs.Material and Methods.The study included 186 patients aged 21–60 years. Independent sequential randomization (1:1) of 173 patients was performed using software. The following parameters were used to evaluate patients: the VA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…This study showed increased range of motion at the operated segment in CTDA group, which is not surprising since mobility preservation after ACDF is caused either by incorrectly performed surgery or by pseudoarthrosis development [ 13 ]. More attention should be paid to range of motion changes in adjacent segments due to possible development of adjacent level syndrome and, as a consequence, the need for repeated surgical intervention [ 14 , 15 ]. Our study demonstrated increased amplitude in adjacent segments after ACDF and decreased amplitude in the caudal segment and no change in the cranial segment in CTDA group.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed increased range of motion at the operated segment in CTDA group, which is not surprising since mobility preservation after ACDF is caused either by incorrectly performed surgery or by pseudoarthrosis development [ 13 ]. More attention should be paid to range of motion changes in adjacent segments due to possible development of adjacent level syndrome and, as a consequence, the need for repeated surgical intervention [ 14 , 15 ]. Our study demonstrated increased amplitude in adjacent segments after ACDF and decreased amplitude in the caudal segment and no change in the cranial segment in CTDA group.…”
Section: Discussionmentioning
confidence: 99%